Pengaruh Keteladanan Guru dan Kebiasaan Shalat Berjamaah Siswa terhadap Sikap Religius Siswa SMPN di Kabupaten Kuantan Singingi Teluk Kuantan - Vita Andani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
This study aims to determine the teacher’s example and the habit of ptaying in congregation of student’s on the religious attitudes of student’s in Junior High Schools in Kuantan Regency Singingi. The population of this study is all student’s Junior High Schools in Kuantan Regency Singingi. Sampling using technique Proportional Random Sampling. This research is a quantitative type of correlation research. The results of the study show that the teacher’s example has a significant influence on student’s religious attitudes marked by obtaining r arithmetic of 0,466 compared to r table of 0,138 wuth a probability value of 0,000, then ha is accepted and h0 is rejected. This study also shows that student’s congregational prayer habits have a significant influence on student’s religious attitudes Marked by obtaining r arithmetic of 0,526, with a probability of 0,000 then ha is accepted and h0 is rejected. This study shows a significant effect between the teacher’s example and the habit of praying in congregation of students simultaneously on student’s religious attitudes Junior High School in Kuantan Regency Singingi. The results of the simultans determination of the dependent variable (r square) of 0,728, the persentase of the influence of variable independent (teachers’s example and student’s prayer habits) on variable dependen (students religious attitude) is 72,8%. TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//